The Influence of Financial Literacy, Income, and Lifestyle on the Interest of Cikarang Factory Employees in Using the SPinjam Feature - Hayati, Inda Nur; Tambunan, Parulian (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to determine the influence of financial literacy, income, and lifestyle on Cikarang factory employees' interest in using the Shopee Pinjam (SPinjam) feature. Based on the results of data collection, processing, testing, and data analysis that have been carried out, as well as the discussions that have been explained, several conclusions have been obtained. The characteristics of respondents were dominated by women, 59 people (55.7%), with the majority of respondents working as entrepreneurs or factory employees, 93 people (87.7%). The majority of respondents had a monthly income of 5 to 7 million rupiah, 43 people (40.3%). Simultaneously, financial literacy, income, and lifestyle have a positive influence on Cikarang factory employees' interest in using the Shopee Pinjam (SPinjam) feature. Partially, each of these variables also has a positive effect on interest in using this feature. Among the three variables, income is the variable that most dominantly influences the interest of Cikarang factory employees in using the Shopee Pinjam (SPinjam) feature.